1990
DOI: 10.2136/sssaj1990.03615995005400030030x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Tillage Effects on the Potassium Status of Some Kentucky Soils

Abstract: Changes in the soil K status occurring as a result of shifting from conventional to no‐tillage management in selected fields were evaluated in this study. The fields were on loess‐ and limestone‐derived soils in western and central Kentucky and have been under no‐tillage management for the last 6 to 16 yr. Two‐ to three‐fold increases in exchangeable and soluble K were evident in most upper surface horizons (Ap1) of soils receiving no‐tillage management, and these increases correlated well with organic matter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…1). Available soil K was higher in the straw incorporated field as has been observed elsewhere (Hoagland and Martin, 1950;Karanthansis and Wells, 1990;Dobermann et al, 1996;Prasad et al, 1999;Singh et al, 2004). It is unusual that soil K declined at similar rates in both fields; certainly, one would expect that it to decline more rapidly in the field where straw was removed.…”
Section: Soil Ksupporting
confidence: 67%
“…1). Available soil K was higher in the straw incorporated field as has been observed elsewhere (Hoagland and Martin, 1950;Karanthansis and Wells, 1990;Dobermann et al, 1996;Prasad et al, 1999;Singh et al, 2004). It is unusual that soil K declined at similar rates in both fields; certainly, one would expect that it to decline more rapidly in the field where straw was removed.…”
Section: Soil Ksupporting
confidence: 67%
“…The need for K is less likely because of the inherent reserve in Moroccan soils (except sandy soils) (Azzaoui et al, 1993). Karathanasis and Wells (1990) found higher exchangeable K under NT due to increased levels of soil organic matter. They recommended reduced application of K fertilizer under NT.…”
Section: Introductionmentioning
confidence: 87%
“…This soil preference will result in more loss of nitrogen under NT and the authors recommended subsurface N fertilizer application and at lower rate. Karathanasis and Wells (1990) found that the changes were prominent in surface horizons, while subsurface or upper subsoil horizons remained unaffected. In our experiment, no K de®ciency was observed even with low K levels below the seed zone under NT (lower than 150 ppm, the critical level).…”
Section: Potassiummentioning
confidence: 95%
“…Both nutrients accumulate near the soil surface due to the cycling of nutrients by plant roots from subsurface to surface soil depths, minimal mixing of organic matter and applied fertilizers with the soil, and the limited vertical mobility ofP and K in the soil profile (Shear and Moschler, 1969;Griffith et aI., 1977;Ketchenson, 1980;Moncrief and Schulte, 1982;Timmons, 1982;Cruse et aI., 1983;Rehm et aI., 1995;Mackay et aI., 1987;Karathanasis and Wells, 1990;Karlen et aI., 1991). The results reported by Shear and Moschler (1969) after 6 years of no-till cropping found P in the upper 5 cm of soil was 3.8 times greater than under conventional tillage, while at greater depths (5-20 cm) conventionally tilled soils possessed twice as much P. Similar results were reported by Karlen et al (1991), Randall (1980), Griffith et al (1977), and Ketchenson (1980) after 12, 10, 6, and 3 years ofno-till cropping.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results reported by Shear and Moschler (1969) after 6 years of no-till cropping found P in the upper 5 cm of soil was 3.8 times greater than under conventional tillage, while at greater depths (5-20 cm) conventionally tilled soils possessed twice as much P. Similar results were reported by Karlen et al (1991), Randall (1980), Griffith et al (1977), and Ketchenson (1980) after 12, 10, 6, and 3 years ofno-till cropping. In Kentucky, five different soils under no-till from 6 to 16 years produced up to three times as much soil exchangeable K and five times as much soluble K in the 5 cm depth of soil compared with the 5-17 cm depth (Karathanasis and Wells, 1990). Nutrient stratification can be a significant problem in drier areas of the Midwest.…”
Section: Literature Reviewmentioning
confidence: 99%